Post-Pandemic Assessment of Parental Involvement in the DREAMS Day Care: Basis for a Proposed Plan of Action - Lunar, Bernardo C.; Maningas, Ma. Gloria T.; Allic, Clarisa M.; Lunar, Noemi (INTI International University, 2023)
The study titled "Post-Pandemic Assessment of Parental Involvement in the DREAMS Day Care: Basis for a Proposed Plan of Action" aimed to evaluate the extent of parental engagement in the DREAMS Day Care Program, a community extension activity of San Pablo Colleges, after the COVID-19 pandemic. Parental involvement is crucial for fostering a supportive and enriching learning environment for young children, particularly during challenging times. This research sought to assess the impact of the pandemic on parental participation and identify potential areas for improvement to develop an action plan for enhanced parental involvement. Using a descriptive-quantitative approach, data was collected from 25 parents through a researcher-made survey questionnaire. The results revealed a very positive extent of parental involvement in various activities related to their child's preschool education. The majority of parents strongly agreed on indicators like active support in learning activities, regular communication with teachers, participation in school events, and discussions with their child about their preschool experiences. The study acknowledges that despite the challenges posed by the pandemic, parents remained actively involved in their child's education. It emphasizes the importance of promoting and supporting parental involvement in early childhood education to create a strong foundation for children's future success and well-being. In order to further enhance parental engagement, the proposed plan of action includes initiatives such as enhancing communication and updates to parents, offering workshops on supporting their child's learning, creating a welcoming and inclusive environment, providing opportunities for parental volunteering, and addressing any barriers hindering parental involvement.